Kesempatan Belajar dan Literasi Matematika Siswa SMA pada Pembelajaran Trigonometri - Nasrullah; Tarisya Septiasa (Program Studi Pendidikan Matematika, FKIP Universitas Muslim Maros, 2026)
This study explores the opportunity to learn (OTL) and mathematical literacy among Grade XI students at SMA Negeri 2 Makassar, with a focus on trigonometry content. Using a qualitative descriptive approach, four students from class XI.5 were purposively selected based on mathematical literacy test results and teacher recommendations: two high-ability students (ST1 and ST2) and two low-ability students (SR1 and SR2). Data were collected through classroom observation, a PISA-based mathematical literacy test comprising six levelled items (Levels 1–6) on trigonometry, and semi-structured interviews. Trustworthiness was established through source triangulation, time triangulation, and member checking. Findings reveal that: (1) students’ OTL encompasses three dimensions, namely content coverage, instructional quality, and learning time; (2) high-ability students demonstrated competencies up to Level 5, while low-ability students reached only Level 1; and (3) high-ability students engaged more extensively with both formal and self-generated learning opportunities, exhibiting self-regulated learning (SRL) behaviors that were largely absent in low-ability peers. These findings suggest that OTL operates in two interacting layers, namely formal (teacher-mediated) and nonformal (student-initiated), with SRL serving as a critical mediating variable. Further research across broader and more varied samples is warranted.